Significance of Ayurvedic Cosmetology in Contemporary Context: A Critical Review - Sharma, Priyanka; Sharma, Manish Kumar (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: The human skin, the body’s largest organ, serves vital functions in physical protection and health reflection. However, modern lifestyle factors often compromise skin health, leading individuals to rely on cosmetic products that may exacerbate damage. Materials and Methods: Ayurveda, an ancient Indian medicinal system, offers holistic approaches to skin care and beauty maintenance, emphasizing internal and external well-being. Ayurvedic texts detail various herbal formulations and practices for skin care, including external applications like Lepa and internal remedies such as Vayasthapan Mahakashaya and Varnya Mahakashaya. Results: Ayurveda addresses a broad spectrum of dermatological concerns, including skin and hair care, fairness, stretch mark elimination, foot care, hair coloring, removal, acne treatment, scar reduction, and dandruff management. These treatments are known for their safety, affordability, and high efficacy. Discussion: This review explores Ayurvedic principles and practices relevant to contemporary dermatological challenges, highlighting its effectiveness in skin care and beauty maintenance. Conclusion: Ayurveda presents promising solutions for modern skin care dilemmas, offering safe, affordable, and effective alternatives to conventional cosmetic products.